2020
DOI: 10.1530/joe-20-0304
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal androgen exposure affects ovarian lipid metabolism and steroid biosynthesis in rats

Abstract: Prenatal androgen exposure affects reproductive functions and has been proposed as an underlying cause of polycystic ovary syndrome (PCOS). In this study, we aimed to investigate the impact of prenatal androgen exposure on ovarian lipid metabolism and to deepen our understanding of steroidogenesis regulation during adulthood. Pregnant rats were hyperandrogenized with testosterone and female offspring were studied when adult. This treatment leads to two different phenotypes: irregular ovulatory and anovulatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…In terms of the effect of androgen on lipid metabolism, Abruzzese et al established a prenatally hyperandrogenized rat model and clarified the effect of prenatal androgen exposure on ovarian lipid metabolism (34). Sun et al compared the steroid and metabolic parameters between women with PCOS and healthy women and found the significantly increased serum androgen levels and upregulated lipid profiles in women with PCOS, which is consistent with previous studies; besides, the cholesterol level was also upregulated in PCOS offspring, indicating that lipid disorders, just like hyperandrogenism and insulin resistance, is a heritable clinical manifestation which may participated in the pathophysiology of PCOS from fetal stage (40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of the effect of androgen on lipid metabolism, Abruzzese et al established a prenatally hyperandrogenized rat model and clarified the effect of prenatal androgen exposure on ovarian lipid metabolism (34). Sun et al compared the steroid and metabolic parameters between women with PCOS and healthy women and found the significantly increased serum androgen levels and upregulated lipid profiles in women with PCOS, which is consistent with previous studies; besides, the cholesterol level was also upregulated in PCOS offspring, indicating that lipid disorders, just like hyperandrogenism and insulin resistance, is a heritable clinical manifestation which may participated in the pathophysiology of PCOS from fetal stage (40).…”
Section: Discussionmentioning
confidence: 99%
“…More specific roles that androgen-induced metabolic disorders played in granulosa cells dysfunction were further demonstrated in the PPI network. Among the 10 hub genes we identified through Cytoscape, the expression of 3-hydroxy-3-methylglutaryl-CoA reductase (HMGCR), a rate-limiting enzyme catalyzing cholesterol production, was decreased in human PCOS granulosa cells and prenatally hyperandrogenized animals ( 34 ), which may be caused by the feedback inhibition of elevated androgen levels in PCOS ( 35 ). Besides, the decline of fatty acid desaturase genes 2 ( FADS2 ) expression was also found in women with PCOS, which was correlated with altered androgen levels and dyslipidemia ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol is a key substrate for the production of androgens, inhibition of the biosynthesis of cholesterol will lead to a decrease of androgens [39][40][41] . In this way, a competitive inhibition of statin to HMG-CoA reductase, a key enzyme of cholesterol biosynthesis, possibly lead to a decrease of androgens [42,43] .…”
Section: Discussionmentioning
confidence: 99%
“…As we all know, Polycystic ovary syndrome (PCOS) is a highly heterogeneous endocrine disorder characterized by hyperandrogen, rare ovulation and polycystic ovary, and its pathogenesis is debated [14][15][16] .Previous studies have demonstrated that the core etiology and primary endocrine characteristics of PCOS are insulin resistance (IR) and hyperandrogenemia (HA), and they can interplay each other leading to metabolic syndrome, especially dyslipidemia [17][18][19][20][21] . AMH are often used as clinical observation indicators reflecting the ovarian reserve 22,23 , and the LH/FSH and T levels were significantly higher in PCOS patients compared with control patients 24,25 .Compared with those characteristics related to PCOS, the expression level of ANGPTL4 in ovarian GCs might be a independent factor which affected incidence of PCOS and could serve as a new predictor for PCOS according to results of ROC cure and binary logistic regression analysis.…”
Section: Discussionmentioning
confidence: 99%